2017
DOI: 10.1016/j.jacr.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Automated Tracking Registry on the Rate of Tracking Failure in Incidental Pulmonary Nodules

Abstract: The automated lung nodule registry tracking system can be exported to other health care facilities and significantly reduces the rate of tracking failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Such insight into department workflows could prove to be of high value and while some uncertainties remain as to which factors influence waiting times, recognising patterns in the data may allow identifying potential causes which then could be further investigated. Other studies showed that an automated lung nodule registry tracking system was able to significantly reduce the tracking failure rate for incidental pulmonary nodules [34].…”
Section: Digitised Workflows Big Data and Artificial Intelligencementioning
confidence: 99%
“…Such insight into department workflows could prove to be of high value and while some uncertainties remain as to which factors influence waiting times, recognising patterns in the data may allow identifying potential causes which then could be further investigated. Other studies showed that an automated lung nodule registry tracking system was able to significantly reduce the tracking failure rate for incidental pulmonary nodules [34].…”
Section: Digitised Workflows Big Data and Artificial Intelligencementioning
confidence: 99%
“…Prospective studies are needed to validate the impact of these updated guidelines on patient outcomes. Second, while the 2017 Fleischner guidelines are likely to significantly reduce the burden of recommended surveillance CT scans for patients and clinicians, adherence to new guidelines is still likely to be poor in usual care settings unless effective tracking and notification systems are established [21,22]. These systems will be increasingly important to monitor guideline concordance as the United States Preventive Services Task Force recommendation for lung cancer screening [23] and the newer Fleischner guidelines, which allow clinicians greater freedom and discretion in determining the need for surveillance, are integrated into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Restructured Clinical and Communication Pathways. Five studies described management strategies that restructured clinical workflow and communication pathways [27][28][29][30][31]. Restructuring strategies altered care delivery in phases 2 through 6 of the clinical pathway.…”
Section: Qualitative Synthesis Of If Management Strategiesmentioning
confidence: 99%